Creating Markets in Angola : Opportunities for Development Through the Private Sector - International Finance Corporation (International Finance Corporation, Washington, DC, 2019)
This Country Private Sector Diagnostic (CPSD) identifies opportunities to stimulate sustainable economic growth and development by harnessing the power of the private sector in Angola. Applying a sectoral lens, it leverages the private sector’s knowledge and experience to accelerate transformational investment. It also puts forward operational recommendations highlighting strategic entry points for diversification and growth, while addressing key constraints to private sector engagement. The CPSD discusses implementation principles inspired by international good practices. It informs World Bank and IFC strategies, paving the way for joint programming to create markets and unlock private sector potential.